A study of the water-holding capacity (WHC) of rabbit meat - Concepcion, Josefa A.; Magluyan, Virginia B. (1977)
The study aims to determine the water-holding capacity (WHC) of rabbit meat as affected by the different factors such as temperature, pH, salt concentration and the addition of phosphate. Results of the experiment showed that the WHC of rabbit meat was lower than that f pork but higher than both of beef chicken meat. Increases of temperature decreased the WHC correspondingly. Increase of pH either to the basic or acidic range caused a slight increase in the ability of the proteins to bind the added water.Addition of salt as well as phosphates up to certain levels gave a marked increase of meat hydration. Combination of salt and phosphate also showed great increases in WHC of the rabbit meat.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Rabbit meat